High surface coverage of a self-assembled monolayer by in situ synthesis of palladium nanodeposits. Issue 35 (31st August 2017) - Herrer, Lucía; Sebastian, Victor; Martín, Santiago; González-Orive, Alejandro; Pérez-Murano, Francesc; Low, Paul J.; Serrano, José Luis; Santamaría, Jesús; Cea, Pilar
Abstract : Nascent metal|monolayer|metal devices have been fabricated by depositing palladium, by growing palladium nanodeposits through a CO-confined growth method. Abstract : Nascent metal|monolayer|metal devices have been fabricated by depositing palladium, produced through a CO-confined growth method, onto a self-assembled monolayer of an amine-terminated oligo(phenylene ethynylene) derivative on a gold bottom electrode. The high surface area coverage (85%) of the organic monolayer by densely packed palladium particles was confirmed by X-ray photoemission spectroscopy (XPS) and atomic force microscopy (AFM). The electrical properties of these nascent Au|monolayer|Pd assemblies were determined from the I – V curves recorded with a conductive-AFM using the Peak Force Tunneling AFM (PF-TUNA™) mode. The I – V curves together with the electrochemical experiments performed rule out the formation of short-circuits due to palladium penetration through the monolayer, suggesting that the palladium deposition strategy is an effective method for the fabrication of molecular junctions without damaging the organic layer.